Metallization paste, electrode and photovoltaic cell manufactured using same
By using medium-temperature cured thick film metallized slurry, including high silver powder and vanadium-containing glass system, the problem of high electrode line resistance of TOPCon/POLO photovoltaic cells under low temperature processes is solved, low resistivity and high adhesion strength are achieved, and the performance and efficiency of photovoltaic cells are improved.
Patent Information
- Application Number
- CN202411757881.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The process limitation of TOPCon/POLO photovoltaic cells is that subsequent steps are required at low temperatures to avoid degraded performance of transparent conductors (TCOs), resulting in higher line resistance of the electrodes, limiting the economics and performance of the electrodes.
A medium-temperature cured thick film metallized slurry is provided, including more than 70% by weight of silver powder, and a vanadium-containing glass system with less than 2.0% by weight of silver powder. The specific surface area of silver powder is 0.7 m2/g to 2.0 m2/g and an average particle size of 0.1 µm to 10 µm. The electrode is manufactured by screen printing and cured at a temperature of 350°C to 500°C.
It achieves low resistivity, high adhesion strength to TCO film and excellent solderability, and improves the filling factor (FF) and overall conversion efficiency of photovoltaic cells.
Smart Images

Figure CN119673522A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of photovoltaic cell equipment, and relates to a metallization paste, an electrode and a photovoltaic cell made using the same, and discloses a screen-printable thick film metallization paste, which is used to make an electrode electrically interconnected with a transparent conductor, and the electrode is used in a photovoltaic cell. The metallization paste contains silver powder and a vanadium-containing glass system that can be cured at a temperature of 350°C to 500°C, and the metallization paste can be used to make an electrode for a transparent conductor of a passivated contact solar cell device (such as a TOPCon type solar cell). Background Art
[0002] Tunnel oxide passivated contact (TOPCon) photovoltaic cells with polysilicon oxide (POLO) contacts have demonstrated efficiencies greater than 25%. Hydrogenated polysilicon (poly-Si) layers and transparent conductive oxide (TCO) layers are deposited on one or both surfaces of a textured, passivated n-type silicon wafer to form a passivated carrier-selective heterocontact. The tunnel oxide deposited directly on the wafer surface provides chemical passivation, resulting in a long minority carrier lifetime. The doped polysilicon layer allows for selective carrier collection, with the p-type doped layer acting as a hole-selective contact and the n-type doped layer acting as an electron-selective contact. The TCO layer enables effective contact between the polysilicon doped layer and the overlying cell electrode, provides lateral conduction, and acts as an anti-reflective coating.
[0003] One performance limitation of TOPCon / POLO technology is that the full-area heterocontact exhibits parasitic light absorption in the TCO film and polysilicon layer.
[0004] Compared to diffused silicon technology, the process limitation of TOPCon / POLO photovoltaic cells is that after the deposition of the polysilicon layer, subsequent steps must be carried out at low temperatures to avoid degradation of the TCO performance. For example, metallization pastes with low curing temperatures must be used.
[0005] The line resistance of low temperature metal / organic metallization pastes (such as metallization pastes with a curing temperature of about 200°C used in, for example, intrinsic thin heterojunction (HIT) photovoltaic cells) can be two to three times higher than the line resistance of high temperature metallization pastes having a peak firing temperature of, for example, about 780°C.
[0006] Electrodes formed using low-temperature metallization pastes have higher line resistance, limiting the economics and performance of electrode configurations.
[0007] Curing metallization pastes used to form electrodes for TOPCon / POLO photovoltaic cells at moderate temperatures, such as about 400°C, can achieve low line resistivity similar to conventional high temperature metallization pastes used for passivated emitter and rear contact (PERC) photovoltaic cells. At moderate temperatures, all organic binders are burned out, and the cure period is longer (such as several minutes) compared to the sub-minute peak firing for high temperature metallization, resulting in higher gridline conductivity.
[0008] In order to provide an economical process for manufacturing high-efficiency TOPCon / POLO photovoltaic cells, a medium-temperature curing thick film metallization paste is needed that can be screen printed to provide a conductive grid with small feature size and high aspect ratio and printability resolution, and exhibit low resistivity, high adhesion strength to TCO film and excellent solderability. The screen printed metallization will also exhibit low specific contact resistance, excellent ideality and high fill factor (FF). Summary of the invention
[0009] The purpose of the present invention is to solve the above problems existing in the prior art, and proposes a metallization paste, an electrode and a photovoltaic cell manufactured using the same.
[0010] The technical solution of the present invention is: The present invention provides a metallization paste, comprising: 70% by weight or more of silver powder; 2.0 wt% or less of vanadium-containing glass systems; The specific surface area (SSA) of the silver powder is 0.7 m 2 / g to 2.0 m 2 / g, average particle size 0.1 µm to 10 µm; The weight % is based on the weight of the metallization paste.
[0011] The specific surface area (SSA) was measured using Brunier-Emmett-Teller (BET) analysis, and the particle size was measured using a particle size analyzer.
[0012] Furthermore, based on the weight of the metallization paste, it also includes: 0.95 wt % or less of a silver powder surfactant coating, and / or 12 wt % or less of an organic carrier.
[0013] Furthermore, the metallization paste comprises: 70 to 95 wt % silver powder; 0.1 wt % to 2.0 wt % of a vanadium-containing glass system; 0.07 wt % to 0.95 wt % of a silver powder surfactant coating, The weight % is based on the weight of the metallization paste.
[0014] Furthermore, the vanadium-containing glass system is prepared from one or more metal oxides; The metal oxide contains vanadium pentoxide in an amount of 10-65 wt % based on the total weight of the metal oxide.
[0015] Furthermore, the metal oxide is any one or a combination of several of vanadium pentoxide V2O5, silver oxide Ag2O, tellurium dioxide TeO2, lead oxide PbO, phosphorus oxide P2O5, and zinc oxide ZnO.
[0016] Furthermore, the vanadium-containing glass system has: Glass transition temperature T from 150°C to 400°C g ; Preferably, the glass transition temperature T g 260° C. to 285° C., wherein the glass transition temperature is measured by differential scanning calorimetry; A softening point of 200°C to 400°C; preferably, a softening point of 280°C to 400°C, wherein the softening point is measured by dilatation method.
[0017] Average particle size from 0.1 µm to 20 µm.
[0018] Furthermore, the vanadium-containing glass system is prepared by the following steps: The metal oxides are combined, the mixture of the metal oxides is heated to 800° C. to 1300° C. for 30 to 100 minutes, and then quenched and subsequently ground to obtain glass particles with a desired diameter and particle size distribution, that is, a vanadium-containing glass system.
[0019] Furthermore, the metallization paste contains 0.5 wt % to 10 wt % of an organic carrier; the organic carrier contains an organic binder, an organic solvent, and one or more additives; the additives include dispersants, thixotropic agents, plasticizers, viscosity stabilizers, defoaming agents, surfactants, pigments, UV stabilizers, antioxidants, coupling agents, and combinations of any of the foregoing.
[0020] Furthermore, the specific surface area of the silver powder is 0.7-1.3 m 2 / g, preferably, the specific surface area of the silver powder is 0.8-1.1 m 2 / g.
[0021] Furthermore, the average particle size of the silver powder is 0.1 µm to 5 µm; Preferably, the average particle size of the silver powder is less than 2.0 µm; More preferably, the average particle size of the silver powder is 0.1 µm to 1.0 µm; Most preferably, the average particle size of the silver powder is 0.7 µm to 0.9 µm.
[0022] Furthermore, the silver powder surfactant coating is selected from any one or a combination of oleic acid, palmitoleic acid, hexadecenoic acid, and cis-10-heptadecenoic acid.
[0023] Furthermore, the curing temperature of the metallization paste is 350°C to 500°C.
[0024] The present invention also provides an electrode prepared by any of the metallization slurries described above.
[0025] Furthermore, the electrode is electrically interconnected with the transparent conductor.
[0026] The present invention also provides an electrode manufacturing method, comprising the following steps: The metallization paste described in any one of the above items is deposited onto a transparent conductor, and cured at a temperature of 350° C. to 500° C. for 5 to 90 minutes to form an electrode electrically interconnected with the transparent conductor.
[0027] Further, the median contact resistivity of the electrical interconnection is less than 10 mΩ·cm; Preferably, the median contact resistivity of the electrical interconnect is less than 5 mΩ·cm; More preferably, the median contact resistivity of the electrical interconnect is less than 3 mΩ·cm.
[0028] Further, the peel strength of the electrode to the transparent conductor is greater than 2N, wherein the pull-out strength is measured using a pull-out strength tester when a copper solder coated strip is soldered to the electrode and the strip is pulled out at 180°.
[0029] Furthermore, the line resistivity of the electrode is less than 3 µΩ·cm.
[0030] Furthermore, the transparent conductor has a thickness of 10 nm to 250 nm.
[0031] Furthermore, the transparent conductor is indium tin oxide.
[0032] The present invention also provides a vanadium-containing electrode manufactured by the electrode manufacturing method described above.
[0033] The present invention also provides a photovoltaic cell comprising a vanadium-containing electrode interconnected with a transparent conductor.
[0034] The present invention further provides an electronic device, comprising any of the electrodes described above.
[0035] Furthermore, the electronic device includes a photovoltaic cell.
[0036] Furthermore, the photovoltaic cell is a tunnel oxide passivation contact photovoltaic cell.
[0037] Furthermore, the photovoltaic cell comprises: A doped crystalline silicon substrate; a tunnel oxide layer covering the doped crystalline silicon substrate; An n+ polysilicon layer covering the tunnel oxide layer; a transparent conductor covering the n+ polysilicon layer; and A vanadium-containing electrode is in contact with the transparent conductor.
[0038] Furthermore, it also includes: a passivation layer covering the n+ polysilicon layer, and the transparent conductor covers the passivation layer.
[0039] Furthermore, the passivation layer contains Al2O3.
[0040] Furthermore, the photovoltaic cell comprises: a doped crystalline silicon substrate; a tunnel oxide layer covering the doped crystalline silicon substrate; A p+ polysilicon layer covering the tunnel oxide layer; a transparent conductor covering the p+ polysilicon layer; and A vanadium-containing electrode is in contact with the transparent conductor.
[0041] Furthermore, it also includes: a passivation layer covering the p+ polysilicon layer, and the transparent conductor covers the passivation layer.
[0042] Furthermore, the passivation layer contains Al2O3.
[0043] Furthermore, the photovoltaic cell comprises: an n-doped silicon substrate comprising a front surface and a back surface; an anti-reflective coating covering the front surface; a tunnel oxide layer covering the back surface, wherein the tunnel oxide layer comprises a first portion and a second portion; an n+ polysilicon layer overlying the first portion of the tunnel oxide layer; a p+ polysilicon layer overlying the second portion of the tunnel oxide layer; A first transparent conductor covering the n+ polysilicon layer; A second transparent conductor covering the p+ polysilicon layer; a first vanadium-containing electrode grid in contact with the first transparent conductor; and A second vanadium-containing electrode grid is in contact with the second transparent conductor.
[0044] Furthermore, the photovoltaic cell comprises: a doped silicon substrate having a front surface and a back surface; a doped emitter layer overlying the front surface; a passivation layer covering the doped emitter layer; an anti-reflection layer covering the passivation layer; an electrode in contact with the doped emitter layer; a tunnel oxide layer overlying the back surface; a doped polysilicon layer covering the tunnel oxide layer; a transparent conductor overlying the doped polysilicon layer; and A vanadium-containing electrode is in contact with the transparent conductor.
[0045] Furthermore, the doped emitter layer includes a p+ doped emitter layer.
[0046] Furthermore, the anti-reflection layer comprises SiN x .
[0047] Furthermore, the electronic device includes a touch panel, a display, a liquid crystal display, a light emitting diode, an organic light emitting device, a photodetector, a photoelectric device, a plasma device, a thin film transistor, an organic electronic device, an electromagnetic radiation sensor, a chemical sensor or a tactile sensor.
[0048] Beneficial effects of the present invention: Compared to conventional Ag powders used in high temperature fired Si solar cells, the proposed Ag powders for contacting transparent conductors or transparent conductive oxides (TCOs) have significantly lower contact resistivity. The optimal Ag powders of the present invention have a median specific contact resistivity r of ~2.25 µΩ·cm when contacting TCOs at intermediate firing temperatures. c , and the particle size D 50 >1.3 mm, SSA less than 0.7 m 2 The median value r obtained from the traditional Ag powder of c is higher, at ~30.4 µΩ·cm.
[0049] Moreover, the proposed silver powder achieves lower line resistivity or higher line conductivity compared to conventional silver powders for higher temperature firing. The median value for the best Ag powder is shown to be ~2.4 µΩ·cm, while the median value for conventional Ag powder is ~37.4 µΩ·cm. These results suggest that the proposed Ag powder should result in solar cells with lower series resistance and higher fill factor (FF) than conventional Ag powder.
[0050] Nano-sized Ag particles are expensive, but the best performance is obtained using the Ag powder provided by the present invention, and the cost of the provided Ag powder is similar to that of conventional fired Ag powder. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] Figure 1 is the contact resistivity box plot; Figure 2 It is a box plot of line resistivity. DETAILED DESCRIPTION
[0052] For the purpose of the following specific embodiments, it should be understood that the embodiments provided by the present application can adopt various alternative changes and step sequences, unless otherwise clearly stated to the contrary. Moreover, unless in any operating example or otherwise stated, all numerals used in the specification and claims to express, for example, the number of components should be understood to be modified by the term "about" in all cases. Accordingly, unless otherwise stated to the contrary, the numerical parameters set forth in the following specification and the attached claims are approximate values, which can vary according to the desired performance obtained by the present invention. At least, but not attempting to limit the application of the principle of equivalents to the scope of the claims, each numerical parameter should at least take into account the number of reported significant figures and be interpreted by applying ordinary rounding techniques.
[0053] Notwithstanding that the numerical ranges and parameters setting forth the broad scope of the invention are approximations, the numerical values set forth in the specific examples are reported as precisely as possible. Any numerical value, however, inherently contains certain errors necessarily resulting from the standard variations found in their respective testing measurements.
[0054] Furthermore, any numerical range recited herein is intended to include all subranges subsumed therein. For example, a range of "1" to "10" is intended to include all subranges between (and including) the recited minimum value of 1 and the recited maximum value of 10, i.e., the minimum value is equal to or greater than 1, and the maximum value is equal to or less than 10.
[0055] For example, in the expression "layer A covers layer B", "overlying" or "overlies" means that one layer is located on and in contact with another layer without any intervening layers, or one layer is located above another layer with one or more intervening layers between the two layers. For example, the expression "layer A covers layer B" means that layer A is located on layer B and in contact with layer B, or there are one or more layers between layer A and layer B. As a specific example, a structure in which the electrode provided in the present application covers a transparent conductor may mean that the electrode is located on top of the transparent conductor and in contact with the transparent conductor without any intervening layers between the electrode and the transparent conductor. A structure in which the electrode provided in the present application covers a transparent conductor may also mean that there are one or more material layers between the electrode and the transparent conductor.
[0056] Reference is now made to the silver powder, metallization paste, electrode, electronic device and method covered by the present invention. The disclosed silver powder, metallization paste, electrode, electronic device and method are not intended to limit the claims. On the contrary, the claims are intended to cover all alternatives, modifications and equivalents.
[0057] The metallization paste provided by the present invention may contain: for example, 70 wt % to 95 wt % of silver powder; 0.1 wt % to 2.0 wt % of a vanadium-containing glass system; and 0.07 wt % to 0.95 wt % of a silver powder surfactant coating, wherein the wt % is based on the weight of the metallization paste.
[0058] The metallization paste provided by the present invention may contain: for example, greater than 85 wt % silver powder; 0.13 wt % to 2.0 wt % vanadium-containing glass system; and 0 wt % to 0.085 wt % silver powder surfactant coating, wherein the wt % is based on the weight of the metallization paste.
[0059] The metallization paste provided by the present invention may contain silver powder or a combination of silver powders.
[0060] The specific surface area (SSA) of the silver powder can be, for example, 0.7 m 2 / g to 1.3 m 2 / g, such as 0.8 m 2 / g to 1.1 m 2 / g, wherein the specific surface area is measured using BET analysis.
[0061] The specific surface area (SSA) of the silver powder may be, for example, less than 2.0 m 2 / g, less than 1.8 m 2 / g, less than 1.6 m 2 / g, less than 1.4 m 2 / g, less than 1.2 m 2 / g or less than 1.0 m 2 / g, wherein the specific surface area is measured using BET analysis.
[0062] The average particle size (D50) of the silver powder can be, for example, 0.1 µm to 10.0 µm, 0.1 µm to 5.0 µm, 0.1 µm to 3.0 µm, 0.1 µm to 2.0 µm, 0.1 µm to 1.0 µm, 0.1 µm to 0.9 µm, 0.5 µm to 0.9 µm, or 0.7 µm to 0.9 µm, wherein the average particle size is measured using a particle size analyzer.
[0063] The average particle size (D50) of the silver powder can be, for example, less than 10.0 µm, less than 5.0 µm, less than 3.0 µm, less than 2.0 µm, less than 1.0 µm, less than 0.9 µm or less than 0.7 µm, wherein the average particle size is measured using a particle size analyzer.
[0064] The firing temperature of the silver powder may be, for example, 350°C to 500°C.
[0065] The silver powder may include a coating comprising a surfactant. The silver powder may include, for example, 0.1 wt % to 1.0 wt % of the surfactant coating, wherein the wt % is based on the total weight of the surfactant-coated silver powder. The coated silver powder may be made during the preparation of the silver powder such that the surfactant is coated on the silver powder during precipitation of the silver powder from the solution.
[0066] The metallization paste provided by the present invention may contain: for example, greater than 70 wt % silver powder, greater than 75 wt %, greater than 80 wt %, greater than 85 wt %, greater than 90 wt %, or greater than 95 wt % silver powder, wherein the wt % is based on the total weight of the metallization paste.
[0067] The metallization paste provided by the present invention may contain, for example, 70 wt % to 95 wt % of silver powder, 75 wt % to 95 wt %, 80 wt % to 90 wt %, or 70 wt % to 80 wt % of silver powder, wherein the wt % is based on the total weight of the metallization paste.
[0068] Specifically, the metallization paste provided by the present invention may contain silver powder in a content range of 70 wt % to 95 wt %, for example, it may be 70 wt %, 72 wt %, 75 wt %, 76 wt %, 78 wt %, 80 wt %, 82 wt %, 83 wt %, 85 wt %, 87 wt %, 90 wt %, 92 wt % or 95 wt %, etc., but is not limited to the listed values, and other values not listed within the range are equally applicable.
[0069] The specific surface area (SSA) of the silver powder was determined using BET analysis and was found to be 0.7 m 2 / g to 2.0m 2 / g, can be 0.7m 2 / g to 1.3m 2 / g, or 0.8m 2 / g to 1.1m 2 / g. Specifically, the specific surface area of the silver powder may be less than 2.0 m 2 / g, less than 1.8 m 2 / g, less than 1.6 m 2 / g, less than 1.4 m 2 / g, less than 1.2 m 2 / g or less than 1.0 m 2 Any value of / g.
[0070] The average particle size (D50) of the silver powder is measured using a particle size analyzer, and can be 0.1 µm to 10.0 µm, 0.1 µm to 8 µm, 0.1 µm to 6 µm, 0.1 µm to 5.0 µm, 0.1 µm to 3.0 µm, 0.1 µm to 2.0 µm, 0.1 µm to 1.0 µm, 0.1 µm to 0.9 µm, 0.5 µm to 0.9 µm, or 0.7 µm to 0.9 µm. Specifically, the average particle size of the silver powder can be any value less than 10.0 µm, less than 5.0 µm, less than 3.0 µm, less than 2.0 µm, less than 1.0 µm, less than 0.9 µm, or less than 0.7 µm.
[0071] The sintering temperature of the silver powder is any value between 350°C and 500°C, for example, it can be 350°C, 360°C, 370°C, 390°C, 400°C, 410°C, 420°C, 440°C, 450°C, 470°C, 480°C or 500°C, but is not limited to the listed values, and other values not listed within the range are also applicable.
[0072] The silver powder may include a coating comprising a surfactant. The silver powder may include, for example, 0.1 wt % to 1.0 wt % of the surfactant coating, wherein the wt % is based on the total weight of the surfactant-coated silver powder. The coated silver powder may be made during the preparation of the silver powder such that the surfactant is coated on the silver powder during precipitation of the silver powder from the solution.
[0073] As an example, the metallization paste provided by the present invention may include a vanadium-containing glass system or a combination of vanadium-containing glass systems.
[0074] The metallization paste provided by the present invention can have a low content of vanadium-containing glass system. For example, the metallization paste can have less than 2.0 wt% of vanadium-containing glass system, less than 1.9 wt%, less than 1.7 wt%, less than 1.6 wt%, less than 1.5 wt%, or less than 1.4 wt% of vanadium-containing glass system, wherein the wt% is based on the total weight of the metallization paste.
[0075] The metallization paste can have, for example, 0.1 wt % to 2.0 wt %, 0.1 wt % to 1.9 wt % of the vanadium-containing glass system, or 0.2 wt % to 1.7 wt %, 0.5 wt % to 1.5 wt %, 0.7 wt % to 1.3 wt %, or 0.8 wt % to 1.2 wt % of the vanadium-containing glass system, wherein the wt % is based on the total weight of the metallization paste.
[0076] Specifically, the metallization paste provided by the present invention may include a vanadium-containing glass system in a content range of 0.1 wt % to 2.0 wt %, for example, it may be 0.1 wt %, 0.2 wt %, 0.5 wt %, 0.6 wt %, 0.8 wt %, 1.0 wt %, 1.2 wt %, 1.3 wt %, 1.5 wt %, 1.7 wt %, 1.9 wt % or 2.0 wt %, etc., but is not limited to the listed values, and other values not listed within the range are equally applicable.
[0077] The vanadium-containing glass system may contain vanadium as an important component in wt %, based on the total weight of the glass system.The vanadium-containing glass system is a vitrified, non-crystalline glass.
[0078] The vanadium-containing glass system can be prepared from a metal oxide composition comprising, for example, 10 wt % to 65 wt % vanadium oxide, V2O5, 10 wt % to 60 wt %, 5 wt % to 50 wt %, 10 wt % to 40 wt %, 10 wt % to 30 wt %, 20 wt % to 60 wt %, 20 wt % to 50 wt %, or 20 wt % to 40 wt % vanadium oxide, V2O5, wherein the wt % is based on the total weight of the metal oxide composition.
[0079] Specifically, the content of vanadium oxide is any value within the range of 10 wt % to 65 wt %, for example, it can be 10 wt %, 15 wt %, 20 wt %, 30 wt %, 40 wt %, 50 wt %, 55 wt %, 60 wt % or 65 wt %, etc., but is not limited to the listed values, and other values not listed within the range are also applicable.
[0080] The metal oxides include, in addition to vanadium pentoxide, silver oxide, tellurium dioxide, lead oxide, phosphorus oxide, zinc oxide, and any one or any combination of the above metal oxides.
[0081] The vanadium-containing glass system can be prepared by combining metal oxides and heating the mixture of metal oxides to a temperature (e.g., 800° C. to 1300° C.) for a time (e.g., 30 minutes to 100 minutes) sufficient to melt the oxides to form a homogenous glass composition. The vanadium-containing glass system is then quenched and subsequently milled to provide glass particles having a desired diameter and size distribution for incorporation into a metallization slurry.
[0082] The vanadium-containing glass system may have a glass transition temperature T of, for example, less than 400° C., less than 350° C., less than 300° C., less than 250° C., or less than 200° C. g .
[0083] The vanadium-containing glass system provided by the present invention may have a glass transition temperature T of, for example, 150°C to 400°C, 150°C to 300°C, 150°C to 200°C, 200°C to 400°C, 200°C to 300°C, 250°C to 400°C, 250°C to 300°C, or 280°C to 400°C. g The glass transition temperature can be measured using differential scanning calorimetry.
[0084] The vanadium-containing glass system may have a glass transition temperature T of, for example, 200° C. to 300° C., such as 225° C. to 290° C. g .
[0085] The vanadium-containing glass system can have a softening point of, for example, 400°C, less than 350°C, less than 300°C, or less than 250°C.
[0086] The vanadium-containing glass system provided by the present invention may have a softening point of, for example, 200° C. to 400° C., 300° C. to 400° C., 250° C. to 400° C., 250° C. to 375° C., 275° C. to 400° C., or 260° C. to 300° C. The softening point may be measured using a dilatometric method.
[0087] The vanadium-containing glass system may have a softening point, for example, less than 380°C, such as 250°C to 380°C.
[0088] The vanadium-containing glass system may have, for example, an average particle size D50 in the range of 0.1 μm to 20 μm (preferably, 0.1 μm to 15 μm, 0.1 μm to 10 μm, or 1 μm to 10 μm), and may be present in the metallization paste in an amount of 0.1 wt % to about 10 wt %, wherein the wt % is based on the total weight of the metallization paste. The average particle size may be measured using a particle size analyzer. The vanadium-containing glass system may have a substantially spherical or irregular shape.
[0089] The vanadium-containing glass system may have electrical conductivity, such as ionic conductivity. For example, the electrical conductivity of the vanadium-containing glass system provided by the present invention at 20° C. may be greater than 1×10 -11 S / cm, greater than 1×10 -10 S / cm, greater than 1×10 -9 S / cm, greater than 1×10 -8 S / cm, or greater than 1×10 -7 S / cm.
[0090] The conductivity of the vanadium-containing glass system at 20°C can be, for example, 1×10 -11 S / cm to 1×10 -7 S / cm, 1×10 - 10 S / cm to 1×10 -8 S / cm, or 1×10 -10 S / cm to 1×10 -9 S / cm.
[0091] The resistivity of the vanadium-containing glass system provided by the present invention at 20°C may be, for example, less than 1×10 11 Ω·cm, less than 1×10 10 Ω·cm, less than 1×10 9 Ω·cm, less than 1×10 8 Ω·cm, or less than 1×10 7 Ω·cm.
[0092] The resistivity of the vanadium-containing glass system at 20°C can be, for example, 1×10 11 Ω·cm to 1×10 7 Ω·cm、1×10 11 Ω·cm to 1×10 8 Ω·cm, or 1×10 11 Ω·cm to 1×10 9 Ω·cm.
[0093] The vanadium-containing glass system can be incorporated into the metallization paste used to make electrodes.
[0094] The metallization paste provided by the present invention can be cured at a temperature of 350° C. to 500° C. to form an electrode. When applied to a transparent conductor that may be damaged during exposure to a temperature above about 500° C., the metallization paste containing the vanadium-containing glass system can be cured to form an electrode interconnected with the transparent conductor without damaging the transparent conductor.
[0095] As an example, the present invention discloses photovoltaic devices including transparent conductors such as transparent conductive oxides. The silver powder, metallization paste, and electrodes can be used with any suitable electronic device including a transparent conductor. Examples of suitable electronic devices include photovoltaic devices, touch panels, liquid crystal displays, light emitting devices, and metallization pastes containing vanadium-containing glass systems can be cured to form electrodes interconnected with the transparent conductor without damaging the transparent conductor diodes (including organic light emitting devices), photodetectors, optoelectronic devices, plasma devices, thin film transistors, organic electronic devices, electromagnetic radiation sensors, chemical sensors, tactile sensors, and flexible electronic devices.
[0096] Furthermore, although reference is made throughout to transparent conductive oxide films, the metallization pastes provided herein can be used to form electrodes for any suitable transparent conductor. These materials and methods are particularly useful in forming interconnects with transparent conductors that would otherwise degrade during exposure to temperatures greater than about 500° C. Examples of suitable transparent conductors include transparent conductive oxides, metal nanostructures (such as metal films), related metal films, conductive grids, metal nanowires, metal meshes, carbon nanotube films, conductive polymer films, polymer dielectric films, organic conductors, graphene films, and combinations of any of the foregoing.
[0097] The transparent conductor can transmit, for example, more than 60% of incident electromagnetic radiation in a desired wavelength range, more than 70%, more than 80%, more than 90%, or more than 95% of incident electromagnetic radiation in a desired wavelength range.
[0098] The thickness of the transparent conductor can be, for example, greater than 1 nm, greater than 10 nm, greater than 20 nm, greater than 50 nm, greater than 100 nm, greater than 150 nm, or greater than 200 nm.
[0099] The transparent conductor may have a thickness of, for example, 1 nm to 250 nm, 1 nm to 200 nm, 5 nm to 100 nm, or 10 nm to 50 nm. The transparent conductor may have a thickness of, for example, less than 250 nm, less than 200 nm, less than 150 nm, less than 100 nm, less than 50 nm, or less than 20 nm.
[0100] The transparent conductor may be a composite conductor, wherein the transparent conductor includes more than one layer of transparent and / or conductive material.
[0101] Transparent conductors can transmit electromagnetic radiation over a narrow or broad wavelength range as appropriate for a particular application. For example, a transparent conductor can be transmissive in at least a portion of the infrared spectrum in the wavelength range of 700 nm to 1 mm, in at least a portion of the visible spectrum in the wavelength range of 400 nm to 700 nm, or in at least a portion of the ultraviolet spectrum in the wavelength range of 10 nm to 400 nm.
[0102] The curing temperature of the metallization paste provided by the present disclosure may be, for example, 350° C. to 500° C., such as 375° C. to 475° C., or 350° C. to 450° C. The curing temperature of the metallization paste provided by the present disclosure may be, for example, less than 500° C., less than 475° C., less than 450° C., less than 425° C., less than 400° C., or less than 375° C. The curing temperature of the metallization paste provided by the present disclosure may be, for example, greater than 350° C., greater than 375° C., greater than 400° C., greater than 425° C., greater than 450° C., or greater than 475° C.
[0103] The organic component of the metallization paste provided by the present invention is selected so that the organic component burns out when exposed to a temperature of less than or equal to 350° C. for a period of, for example, 5 minutes to 90 minutes. The organic component can be selected so that the organic component burns out when exposed to a temperature of, for example, less than or equal to 350° C., less than 300° C., less than 275° C., less than 250° C., less than 225° C., or less than 200° C. for a period of, for example, 1 minute to 90 minutes (e.g., 5 minutes to 90 minutes, or 10 minutes to 60 minutes).
[0104] The inorganic components (such as metal powder and vanadium-containing glass system) of the metallization paste provided by the present invention can be selected so that the inorganic components melt or solidify to form a strong interconnection at a temperature less than 500°C, thereby avoiding degradation of properties such as sheet resistance of the underlying transparent conductor.
[0105] As an example, the medium temperature metallization paste provided by the present invention can be used to form electrodes for TOPCon / POLO and IBC photovoltaic cells.
[0106] Generally, for photovoltaic cell electrode applications, a thick film metallization slurry is used to form a conductive grid or metal contact. The thick film metallization slurry may include a silver powder suspension, a vanadium-containing glass system, a silver powder surfactant coating, and an organic vehicle. The vanadium-containing glass system is used to bond the functional / conductive phase to the silicon wafer after thermal treatment. For conventional silicon photovoltaic cells with silicon nitride anti-reflective coatings, the glass system may also be used to etch through the anti-reflective layer and the passivation layer to provide an ohmic contact between the electrode and the silicon surface of the photovoltaic cell.
[0107] For TOPCon / POLO photovoltaic cells, the electrodes can be brought into direct contact with transparent conductors (such as TCO films); therefore, vanadium-containing glass systems cannot be used as etchants. The carrier is an organic system that acts as a rheological carrier to control the fluidity and printability of the paste. The organic carrier consists of resins, solvents, and additives. The properties of the metallization paste, especially the front silver-containing metallization paste, are important for achieving high-efficiency photovoltaic cells. Therefore, the quality and performance of the metallization paste affect the economic viability of the photovoltaic system. The screen printing technology currently used for most photovoltaic cells is being further developed for printing fine-line conductive grids to reduce silver consumption and thereby reduce costs, reduce shading and thereby increase current density, and improve photovoltaic module performance.
[0108] To maintain high efficiency over the long term, it is important that the pull-off strength and adhesion of the PV cell metallization to the underlying surface (such as a transparent conductor) are strong. Achieving both high pull-off strength is challenging because as the adhesion strength increases by increasing the amount of glass system in the metallization paste that acts as a binder, the contact resistance of the electrode also increases, resulting in a decrease in the fill factor (FF) and overall conversion efficiency of the PV cell. Increasing the glass content in the metallization paste reduces solderability and, in the case of non-conductive glass systems, increases contact resistivity and reduces the fill factor (FF).
[0109] The electrodes may be formed using a metallization paste that can be cured at moderate temperatures, such as temperatures between 350°C and 500°C.
[0110] The medium temperature metallization paste provided by the present invention may contain a vanadium-containing glass system.
[0111] The metallization paste provided by the present invention can be used to make electrical interconnections with transparent conductors. For example, the transparent conductor can be a transparent conductive oxide film, such as the TCO film used in TOPCon / POLO photovoltaic cells.
[0112] The metallization paste provided by the present invention can have good wettability to a transparent conductor (such as a TCO film). Good wettability means that when heated to a flow point temperature or above, the contact angle of the metallization paste on the transparent conductor (such as a TCO film) is less than 30°. Due to capillary action, the metallization paste can flow to contact the interface, thereby forming good adhesion between the cured metallization paste and the transparent conductor (such as a TCO film).
[0113] The curing temperature of the metallization paste provided by the present invention can be, for example, 350° C. to 500° C., such as 375° C. to 475° C., or 350° C. to 450° C. That is, the metallization paste provided by the present invention can be cured at a certain temperature (for example, 350° C. to 500° C., such as 400° C. to 450° C. or 375° C. to 425° C.) for a duration of 5 minutes to 90 minutes, preferably, for example, 10 minutes to 60 minutes or 20 minutes to 40 minutes.
[0114] The curing temperature of the metallization paste provided by the present invention may be, for example, less than 500°C, less than 475°C, less than 450°C, less than 425°C, less than 400°C, or less than 375°C.
[0115] The curing temperature of the metallization paste provided by the present invention can be, for example, greater than 350°C, greater than 375°C, greater than 400°C, greater than 425°C, greater than 450°C, or greater than 475°C.
[0116] When the metallization paste is cured at a certain temperature (e.g., less than or equal to 350° C., less than 300° C., less than 250° C., or less than 200° C.), the organic material in the metallization paste provided by the present invention will burn off. The metallization paste provided by the present invention can be cured without etching or damaging the underlying transparent conductor.
[0117] As an example, the metallization slurry provided by the present invention may include a silver powder suspension, a vanadium-containing glass system, a silver powder surfactant coating and an organic vehicle. The organic vehicle may include an organic binder, an organic solvent, a dispersant and one or more additives, such as a rheology modifier. The inorganic components of the metallization slurry may include a glass system and a conductive metal provided by the present invention.
[0118] The metallization paste can include, for example, less than 12 wt % organic vehicle, or less than 10 wt %, less than 8 wt %, less than 6 wt %, or less than 4 wt % organic vehicle, wherein the wt % is based on the total weight of the metallization paste.
[0119] The metallization paste may include, for example, 1-12 wt % of an organic vehicle, or 2-11 wt %, 3-10 wt %, or 4-8 wt % of an organic vehicle, wherein the wt % is based on the total weight of the metallization paste.
[0120] Specifically, based on the total weight of the metallization paste, the content of the organic carrier is any value in the range of 1-12 weight %, for example, it can be 1 weight %, 2 weight %, 4 weight %, 5 weight %, 7 weight %, 8 weight %, 9 weight %, 10 weight % or 12 weight %, etc., but is not limited to the listed values, and other values not listed in the range are also applicable.
[0121] The organic vehicle may contain, for example, 1-25 wt % of an organic binder, such as 5-20 wt % or 10-15 wt % of an organic binder, wherein the wt % is based on the total weight of the organic vehicle. The organic vehicle may contain, for example, 1-85 wt % of a solvent, such as 10-75 wt % or 20-65 wt % of a solvent, wherein the wt % is based on the total weight of the organic vehicle.
[0122] As an example, the metallization paste provided by the present invention may contain, for example, more than 90 wt % of silver powder, less than 1.9 wt % of vanadium-containing glass system, and less than 10 wt % of organic vehicle, wherein the wt % is based on the total weight of the metallization paste.
[0123] The metallization paste provided by the present invention may contain, for example, 90 wt % to 99 wt % of silver powder, 0.1 wt % to 1.9 wt % of a vanadium-containing glass system, and 0.5 wt % to 10 wt % of an organic vehicle, wherein the wt % is based on the total weight of the metallization paste.
[0124] The metallization paste provided by the present invention may contain, for example, 90 wt % to 98 wt % of silver powder, 0.5 wt % to 1.5 wt % of a vanadium-containing glass system, and 1 wt % to 8 wt % of an organic vehicle, wherein the wt % is based on the total weight of the metallization paste.
[0125] The metallization paste provided by the present invention may contain, for example, 90 wt % to 97 wt % of silver powder, 0.7 wt % to 1.2 wt % of a vanadium-containing glass system, and 2 wt % to 7 wt % of an organic vehicle, wherein the wt % is based on the total weight of the metallization paste.
[0126] The metallization paste provided by the present invention may include silver powder as the main conductive particle. The average particle size D50 of the silver powder may be, for example, 0.1 μm to 10 μm, 0.1 μm to 8 μm, 0.1 μm to 6 μm, 0.1 μm to 4 μm, or 0.1 μm to 2 μm. The silver powder may include a combination of a silver powder portion and different silver particles, which are characterized by different average particle sizes.
[0127] The average particle size D50 of the silver powder can be, for example, 0.1 μm to about 10 μm, or 0.5 μm to 5 μm. The average particle size can be measured by dispersing the silver powder in isopropanol at 25° C. for 3 minutes by ultrasonic treatment, for example, using a Horiba LA-960 particle size analyzer. Within this range of average particle diameters, the composition can provide low contact resistance and low line resistance.
[0128] The silver powder may have a spherical, flaky or amorphous shape, or a combination of any of the foregoing.
[0129] The metallization paste provided by the present invention may contain, for example, 88 wt % to 99 wt % of silver powder, 91 wt % to 98 wt %, 92 wt % to 97 wt %, or 93 wt % to 96 wt % of silver powder, wherein the wt % is based on the total weight of the metallization paste.
[0130] Glass systems can be used to enhance the adhesion between silver powder and transparent conductors.
[0131] The metallization paste provided by the present invention may contain an organic binder, an organic solvent, an additive, or a combination of any of the foregoing.
[0132] The metallization paste provided by the present invention may include: for example, 0.05 wt % to 10 wt % of an organic binder; 1 wt % to 20 wt % of a solvent; and 0.01 wt % to 1 wt % of one or more additives, wherein the weight % is based on the total weight of the metallization paste. As an example, the metallization paste may include an organic binder or a combination of organic binders.
[0133] Organic binders can be used to impart desired viscosity and / or rheological properties to metallization pastes to facilitate screen printing of photovoltaic cell electrodes. Organic binders can also promote uniform dispersion of inorganic components in printable metallization pastes.
[0134] Suitable organic binders include, for example, acrylate resins and cellulosic resins, such as ethyl cellulose, ethyl hydroxyethyl cellulose, nitrocellulose, mixtures of ethyl cellulose and phenolic resins, alkyd resins, phenolic resins, acrylates, xylene, polybutane, polyesters, ureas, melamine, vinyl acetate resins, wood rosin, alcohol polymethacrylates, and combinations of any of the foregoing.
[0135] Other suitable resins include, for example, ethyl cellulose, cellulose esters (CAB, CAP), polyacrylates, (modified) polysiloxanes, polyvinyl butyral (PVB), polyvinyl pyrrolidone (PVP), saturated polyesters, non-reactive polyamides (PA), modified polyethers, and combinations of any of the foregoing. Other resins characterized by moderate polarity may also be used. The organic resin may include ethyl cellulose.
[0136] The organic binder may be present in an amount of, for example, 0.1 wt % to 10 wt %, 0.1 wt % to 8 wt %, 0.2 wt % to 6 wt %, 0.5 wt % to 5 wt %, or 0.1 wt % to 5 wt %, wherein the wt % is based on the total weight of the metallization paste.
[0137] As an example, the metallization paste may include an organic solvent or a combination of organic solvents.
[0138] Organic solvents may be used to impart solubility, dispersibility, and / or coupling properties to the metallization paste.
[0139] Examples of suitable organic solvents include: terpineol, glycol ethers, glycol acetate, Texanol® (ester alcohol), tributyl citrate, O- Acetyl tributyl citrate, DBE® ester (a mixture of dimethyl adipate, dimethyl glutarate and dimethyl succinate); dimethyl phthalate (DMP), and any combination of the foregoing. Suitable organic solvents may have, for example, a boiling point greater than 200°C and an evaporation rate less than 0.01 at 23°C. Suitable organic solvents may be oxygenated solvents, including: alcohols, such as ethanol, methanol, butanol, n-propanol, isobutanol, and isopropanol; esters, such as ethyl acetate, n-butyl acetate, n-propyl acetate, and isopropyl acetate; and ketones, such as acetone, diacetone alcohol, isophorone, cyclohexanone, methyl ethyl ketone, and methyl isobutyl ketone. Other suitable organic solvents, such as ethers, alcohols and / or esters, may also be used.
[0140] In certain embodiments, the organic solvent comprises a glycol ether.
[0141] Other examples of suitable solvents include hexane, toluene, ethyl cellulose (ethyl cellusolve®), cyclohexanone, butyl cellulose (butyl cellusolve®), butyl carbitol (diethylene glycol monobutyl ether), dibutyl carbitol (diethylene glycol dibutyl ether), carbitol butyl acetate (diethylene glycol monobutyl ether acetate), propylene glycol monomethyl ether, hexylene glycol, terpineol, methyl ethyl ketone, benzyl alcohol, gamma-butyrolactone, ethyl lactate, and combinations of any of the foregoing.
[0142] The metallization paste provided by the present invention may contain: 1 wt % to 20 wt %, 1 wt % to 10 wt %, 1 wt % to 6 wt %, or 1 wt % to 5 wt % of an organic solvent, wherein the wt % is based on the total weight of the metallization paste.
[0143] As an example, the metallization paste may also include additives for modifying the physical properties of the paste, such as to enhance fluidity, processing characteristics, and stability. The additives may include: dispersants, thixotropic agents, plasticizers, viscosity stabilizers, defoamers, surfactants, pigments, UV stabilizers, antioxidants, coupling agents, and any combination of the foregoing.
[0144] The additive or combination of additives may be present in the composition in an amount, for example, from 0.005 wt % to about 3 wt %, from 0.1 wt % to 1.5 wt %, from 0.2 wt % to 1.5 wt %, or from 0.3 wt % to 1 wt %, wherein the wt % is based on the total weight of the metallization paste.
[0145] As an example, the metallization paste provided by the present invention may contain: for example, 70 wt % to 95 wt % of silver powder, 0.1 wt % to 2.0 wt % of a vanadium-containing glass system, and 0.07 wt % to 0.95 wt % of a silver powder surfactant coating, wherein the wt % is based on the total weight of the metallization paste.
[0146] The metallization paste provided by the present invention may contain, for example, 75 wt % to 92 wt % of silver powder, 0.1 wt % to 1.9 wt % of a vanadium-containing glass system, and 0.075 wt % to 0.92 wt % of a silver powder surfactant coating, wherein the wt % is based on the total weight of the metallization paste.
[0147] The metallization paste provided by the present invention may contain, for example, 80 wt % to 90 wt % of silver powder, 0.1 wt % to 1.7 wt % of a vanadium-containing glass system, and 0.08 wt % to 0.9 wt % of a silver powder surfactant coating, wherein the wt % is based on the total weight of the metallization paste.
[0148] For screen printing fine lines with high aspect ratios, it may be expected that the viscosity of the metallization paste provided by the present invention may be, for example, 500 poise to 7000 poise at a temperature of 15°C to 50°C, as measured using a viscometer with a spindle speed of 10 rpm.
[0149] The viscosity of the metallization slurry provided by the present invention can be, for example, in the range of 50 Pa-sec to 700 Pa-sec, as measured using a Brookfield DV-III+ viscometer with an SC4-14 spindle at 10 rpm and a temperature of 25°C. The metallization slurry provided by the present invention can be used to manufacture an electrode with a high aspect ratio. For example, an electrode with a high aspect ratio can be characterized by, for example, an aspect ratio greater than 0.2, greater than 0.3, greater than 0.4, greater than 0.5, greater than 0.6, greater than 0.7, greater than 0.8, greater than 0.9, or greater than 1, wherein the aspect ratio refers to the line height divided by the line width. The aspect ratio of the electrode can be, for example, 0.3 to 1, 0.4 to 0.8, 0.4 to 0.6, 0.5 to 1, or 0.5 to 0.8.
[0150] Metallization paste can be prepared using the following method: The vanadium-containing glass system can be prepared by combining metal oxides to form a metal oxide composition, melting the metal oxide composition to form glass, quenching the glass, and grinding the quenched glass to provide a vanadium-containing glass system having a desired average particle size and dispersion.
[0151] The organic vehicle can be prepared by mixing a solvent or solvent mixture with one or more organic resins, a plasticizer, a defoamer, and additives such as a rheological thixotropic additive and heating.
[0152] Silver powder may be combined with an organic vehicle, a glass system, and other additives and mixed thoroughly to form a metallization paste.
[0153] The metallization slurry may then be milled to obtain the desired dispersion of the inorganic components.The metallization slurry may then be filtered to remove any unwanted large particles.
[0154] As an example, the metallization paste may be applied to the surface of a silicon photovoltaic cell by screen printing.
[0155] The metallization paste provided by the present invention is intended to be directly applied to a transparent conductor. The screen used in screen printing can be an emulsion-covered mesh that is patterned to form a grid pattern. The number of meshes can be, for example, 300 to 400 meshes, or 325 to 380 meshes, and the diameter of the mesh wire (which can be stainless steel) can be about 0.3 mil to 1.5 mils (7.62 μm to 38.1 μm), such as 0.7 mil to 1.1 mils (17.78 μm to 27.94 μm) in diameter. Other screens and mesh sizes can be used as appropriate for specific metallization pastes, process conditions, and desired feature sizes.
[0156] The metallization paste deposited in the form of electrical conductors such as gridlines may have a width of, for example, 0.5 mil to 4 mils (12.7 µm to 101.6 µm) and a height of 0.1 mil to 1.5 mils (2.54 µm to 38.1 µm). The deposited metallization paste may be in the form of busbars.
[0157] After being applied to the surface of the photovoltaic cell, the screen-printed metallization paste can be dried, for example, by heating the applied metallization paste at a temperature of 100° C. to 200° C. for a period of time (e.g., 2 minutes to 10 minutes). The dried metallization paste is then cured at a temperature of less than 500° C. (350° C. to 450° C.) for a period of 5 minutes to 90 minutes, thereby providing photovoltaic cell electrodes, such as grid lines and busbars.
[0158] Electrodes with dimensions of 1.2 mm width and 16 µm height may exhibit a line resistivity of less than 3 µΩ·cm and may exhibit an adhesion strength of at least 2N on a transparent conductor such as a TCO film, where the conductivity is measured by a line resistivity electrical probe measurement and the adhesion strength is measured by a 180 degree solder tab pull test. For background, Ag thick film busbars with a resistivity of 3 µΩ·cm or less and an adhesion strength greater than 1.5N are generally considered acceptable for use in the photovoltaic cell industry.
[0159] The electrodes may be, for example, busbars or gridlines. The busbars may be weldable. The gridlines may not necessarily be weldable. Thus, the glass system and metallization layers used to form the busbars may have a different composition than the gridlines.
[0160] The photovoltaic electrode prepared using the metallization paste provided by the present invention may have a line resistivity of, for example, less than 3 µΩ·cm, less than 2.75 µΩ·cm, less than 2.5 µΩ·cm, less than 2.2 µΩ·cm, or less than 2.0 µΩ·cm.
[0161] The pull-out strength of the photovoltaic cell electrode prepared using the metallization paste provided by the present invention on the transparent conductor on the silicon wafer substrate can be, for example, greater than 2N, greater than 2.5N, or greater than 3N, wherein the peel strength is measured according to a 180° angle pull-out test.
[0162] Electrodes prepared from the metallization slurry provided by the present invention can maintain acceptable conductivity and adhesion strength after exposure to accelerated environmental test conditions (including damp heat test and accelerated heat test), which are used to identify the 25-year service life of photovoltaic cells.
[0163] The metallization paste provided by the present invention can be applied to the transparent conductor of the photovoltaic cell and cured to provide electrical conductors such as grid lines and busbars. Therefore, according to the present invention, the photovoltaic cell includes an electrode formed by the metallization paste provided by the present application. The photovoltaic cell may include an electrode formed by the metallization paste, and the electrode includes the glass system provided by the present application.
[0164] The cured electrode provided by the present invention does not contain organic materials. During the curing of the metallization paste, as the temperature rises to a curing temperature of 360° C. to 500° C., the organic material used to form the electrode in the metallization paste is burned off, for example, at a temperature of 150° C. to 380° C. For example, the cured electrode provided by the present invention may contain less than 1% by weight of organic materials, less than 0.1% by weight of organic materials, or less than 0.01% by weight of organic materials, wherein the % by weight is based on the weight of the electrode.
[0165] The metallization paste provided by the present invention can be applied to a substrate such as a silicon substrate or a transparent conductor on a silicon substrate in the form of an electrode. Then, the metallization paste can be cured to form an electrode.
[0166] Electrodes (such as photovoltaic cell electrodes) can be prepared from the metallization paste provided by the present invention.
[0167] The metallization paste provided by the present invention can be used in a medium temperature metallization paste for electrical contact with a transparent conductor such as a TCO film. Examples of suitable materials for TCO films include: In2O3:H (IO:H), InSnO (ITO), InZnO (a-IZO), In2O3:Zr (ZrIO); ZnO:Al (AZO), ZnSnO (a-ZTO), ZnO:B (BZO), ZnO:B (BZO), ZnO:Ga (GZO), SnO2, ZnO, CdSnO2, and CdO:In. For example, the TCO film can be an indium tin oxide (ITO) film. The TCO film (such as an ITO film) can have a thickness of, for example, 1 nm to 250 nm, 10 nm to 250 nm, 20 nm to 200 nm, or 20 nm to 80 nm, and a refractive index of about 2.0.
[0168] The electronic device provided by the present invention (such as a photovoltaic cell) may include an electrode prepared from a metallization paste containing the glass system provided by the present invention.
[0169] The photovoltaic cell may have electrodes such as grid lines, bus bars or other conductive contact layers including the cured metal paste provided by the present invention.
[0170] The electrodes may contact a transparent conductor such as an indium tin oxide layer.
[0171] The metallization paste provided by the present invention can be directly coated on a transparent conductor and can be cured to form an electrode without damaging the transparent conductor.
[0172] The electrode provided by the present invention can be in electrical contact with the tunnel oxide layer.
[0173] The metallization paste provided by the present invention can be used to manufacture electrodes on tunnel oxide passivation contact (TOPCon) photovoltaic cells.
[0174] As an example, the photovoltaic cell provided by the present invention may include: for example, a doped crystalline silicon substrate, a tunnel oxide layer covering the doped crystalline silicon substrate, an n+ polycrystalline silicon layer covering the tunnel oxide layer, a transparent conductor covering the n+ polycrystalline silicon layer; and an electrode prepared by the metallization paste provided by the present invention, which is in contact with the transparent conductor.
[0175] The photovoltaic cell provided by the present invention may include: a doped crystalline silicon substrate, a tunnel oxide layer covering the doped crystalline silicon substrate, a p+ polycrystalline silicon layer covering the tunnel oxide layer, a transparent conductor covering the p+ polycrystalline silicon layer; and an electrode prepared by the metallization paste provided by the present invention, the electrode being in contact with the transparent conductor. The photovoltaic cell may also include a passivation layer covering the p+ polycrystalline silicon layer, such as an aluminum oxide Al2O3 passivation layer, and the transparent conductor covering the passivation layer.
[0176] The photovoltaic cell provided by the present invention may include: an n-doped silicon substrate, which includes a front surface and a back surface; a tunnel oxide layer, which covers the back surface, wherein the tunnel oxide layer includes a first part and a second part; an n+ polysilicon layer, which covers the first part of the tunnel oxide layer; a p+ polysilicon layer, which covers the second part of the tunnel oxide layer; a first transparent conductor, which covers the n+ polysilicon layer; a first electrode grid, which contacts the first transparent conductor covered on the n+ polysilicon layer, wherein the first electrode grid includes an electrode prepared by the metallization paste provided by the present invention; and a second electrode grid, which contacts the second transparent conductor covered on the p+ polysilicon layer, wherein the second electrode grid includes an electrode prepared by the metallization paste provided by the present invention.
[0177] The photovoltaic cell provided by the present invention may include: a doped silicon substrate having a front surface and a back surface, a doped emitter layer covering the front surface, a passivation layer covering the doped emitter layer, an anti-reflection layer covering the passivation layer, a diffusion electrode in contact with the doped emitter layer, a tunnel oxide layer covering the back surface, an n+ plus polysilicon layer covering the tunnel oxide layer, a transparent conductor covering the n+ polysilicon layer, and an electrode prepared by the metallization paste provided by the present invention, the electrode being in contact with the transparent conductor. The doped emitter layer may be, for example, a p+ doped emitter layer or an n+ doped emitter layer. The anti-reflection layer may contain silicon nitride SiN x , such as Si3N4. A passivation layer may be overlaid on the n+ polysilicon layer, and a transparent conductor may be overlaid on the passivation layer. The passivation layer includes Al2O3.
[0178] Photovoltaic cells with electrodes made of the metallization paste provided by the present invention can be incorporated into photovoltaic modules and photovoltaic systems. The present invention covers photovoltaic modules and photovoltaic systems comprising one or more photovoltaic cells, the photovoltaic cells comprising the photovoltaic cell electrodes provided by the present invention, the photovoltaic cell electrodes prepared by the method provided by the present invention, the photovoltaic cell electrodes prepared using the metallization paste provided by the present invention, and / or the photovoltaic cell electrodes prepared using the glass system provided by the present invention.
[0179] The devices provided by the present invention include devices having a transparent conductor and an electrode provided by the present invention interconnected with the transparent conductor. The electrode can be made using a vanadium-containing metallization paste provided by the present invention that can be cured at a temperature of 350° C. to 500° C. Examples of devices incorporating transparent conductors include photovoltaic devices, touch panels, displays, liquid crystal displays, light-emitting diodes (including organic light-emitting devices), photodetectors, optoelectronic devices, plasma devices, thin film transistors, organic electronic devices, electromagnetic radiation sensors, chemical sensors, and tactile sensors. Example
[0180] The embodiments provided in the present application are further described with reference to the following examples, which describe metallization pastes and photovoltaic cell electrodes according to the present invention. It will be apparent to those skilled in the art that many modifications can be practiced both to materials and methods without departing from the scope of the present application.
[0181] Vanadium-containing glass system Metal oxides including vanadium oxide V2O5 are combined and heated to 800°C to 1300°C to melt the oxides. The vanadium-containing glass is cooled to room temperature. The glass is then milled to provide a fine glass particle distribution. The glass system is characterized by an average particle size D50 measured using a Mastersizer 3000 laser diffraction particle size analyzer, wherein the average particle size is 2 µm.
[0182] Determination of the glass transition temperature T of glass systems by differential scanning calorimetry g The glass transition temperature of the vanadium-containing glass system is between 150°C and 300°C, depending on the vanadium-containing glass system.
[0183] Depending on the vanadium-containing glass system, the softening point of the vanadium-containing glass system is between 200° C. and 400° C., wherein the softening point is determined by dilatography and is defined as the temperature at which the glass system begins to flow under its own weight. Example 1
[0184] Preparation of vanadium-containing glass system Metal oxides including vanadium oxide are combined and heated to a temperature of 1000°C to melt the oxides. The vanadium-containing glass is cooled to room temperature. The glass is then milled to provide a fine glass particle distribution. The glass system is measured using a Mastersizer 3000 laser diffraction particle size analyzer, and the average particle size is 2 µm.
[0185] Determination of the glass transition temperature T of vanadium-containing glass systems by differential scanning calorimetry g is 200℃.
[0186] The softening point of the vanadium-containing glass system was determined by dilatography to be 300° C., defined as the temperature at which the glass system begins to flow under its own weight. Example 2
[0187] Preparation of vanadium-based glass system Metal oxides including vanadium oxide are combined and heated to a temperature of 800°C to melt the oxides. The vanadium-containing glass is cooled to room temperature. The glass is then milled to provide a fine glass particle distribution. The glass system is measured using a Mastersizer 3000 laser diffraction particle size analyzer, and the average particle size is 2 µm.
[0188] Determination of the glass transition temperature T of vanadium-containing glass systems by differential scanning calorimetry g is 150°C.
[0189] The softening point of the vanadium-containing glass system was determined by dilatography to be 200° C., defined as the temperature at which the glass system begins to flow under its own weight. Example 3
[0190] Preparation of vanadium-based glass system Metal oxides including vanadium oxide are combined and heated to a temperature of 1300°C to melt the oxides. The vanadium-containing glass is cooled to room temperature. The glass is then milled to provide a fine glass particle distribution. The glass system is measured using a Mastersizer 3000 laser diffraction particle size analyzer, and the average particle size is 2 µm.
[0191] Determination of the glass transition temperature T of vanadium-containing glass systems by differential scanning calorimetry g is 300℃.
[0192] The softening point of the vanadium-containing glass system was determined by dilatography to be 400°C, defined as the temperature at which the glass system begins to flow under its own weight. Example 4
[0193] Metallization paste containing vanadium-based glass system A metallization paste containing a glass system was prepared. The nominal content of the metallization paste is shown in Table 1.
[0194] Table 1 Composition of metallization paste Material Product Number source Content (weight %) Silver powder ‒ ‒ 90-99 Glass system See Example 1 GF1 0.1+1.9 Adhesives Ethocel® Ethylcellulose STD4 Dow Chemical 0.05-10 Solvent Glycol Ether The Dow Chemical Company 1-20 Thixotropic Additives Thixatrol® ST Elementis 0.5 Dispersants Disperbyk® 102 BYK-chemie 0.2 At 60° C., an organic binder, 1.0 wt % of Ethocel® ethylcellulose (STD4, The Dow Chemical Company) was dissolved in 6.69 wt % of ethylene glycol ether, and 89 wt % of spherical silver particles (AG-4-8, DOWA Hightech Co., Ltd.) having an average particle size (D50) of 2.0 µm, 2.5 wt % of the vanadium-containing glass system in Example 1 having an average particle size (D50) of 1.0 µm, 0.4 wt % of a dispersant (Disperbyk® 102, BYK-Chemie), and 0.4 wt % of a thixotropic agent (Thixatrol® ST, Elementis Ltd.) were added to the binder solution, followed by mixing and kneading in a three-roll kneader to prepare a screen-printable metallization paste.
[0195] The metallization paste is deposited by screen printing in a predetermined pattern on the front surface of a silicon wafer with a transparent conductive oxide (TCO) anti-reflective coating, with a doped reflector having a sheet resistance of 45Ω / sq as the bottom layer, and then dried in an infrared (IR) oven at 150°C. The photovoltaic cells formed according to this procedure are cured in a belt baking oven at a temperature of 350°C to 450°C for a period of 10 minutes to 30 minutes.
[0196] The metallization paste is also screen printed onto a single crystal silicon wafer to provide a line of 40 µm wide and 20 µm high. The metallization paste is then fired at a temperature of about 400°C for about 20 minutes to provide a sintered ohmic contact for the photovoltaic cell electrode metallization layer.
[0197] The resistivity, pull-out strength and weldability of the electrodes prepared from the metallization paste were measured. The line resistivity was measured using an ohmmeter and calculated based on the size of the electrode. The pull-out strength was measured using a Mark-10 pull-out strength tester, in which a copper solder-coated strip was welded to a photovoltaic cell busbar and the strip was pulled at 180°. The weldability was qualitatively evaluated. Poor weldability refers to a sheet welding area less than or equal to 30%. Qualified weldability refers to a welded electrode top surface area of 70% to 90%. Poor weldability refers to a welded electrode top surface area less than 70% and greater than 30%. Excellent weldability refers to a welded top surface area greater than 90%. The area of the welded surface can be measured by visual microscopy. Good weldability is also reflected in the failure mode of the pull-out test. When pulled with a force greater than 2N, the solder joint should not fail.
[0198] The median contact resistivity of electrodes prepared using silver powder most suitable for medium temperature firing is about 2.27 mΩ·cm, while the median contact resistivity of electrodes containing silver powder with an average particle size ranging from 1.5 µm to 2.0 µm used in high temperature silver-containing metallization pastes is about 30.41 mΩ·cm.
[0199] This result is unique and unexpected because typically for conventional solar cell front electrode silver powders used for high temperature firing, the best performing silver powders have lower SSAs (typically around 0.35-0.5 μm). 2 / g, where particle size D 50 in the range of 1.5 µm to 2 µm).
[0200] Compared to conventional Ag powders used in high temperature fired Si solar cells, the Ag powders proposed in the present invention for contacting transparent conductors or transparent conductive oxides (TCOs) have significantly lower contact resistivity. The best Ag powders of the present invention have a median specific contact resistivity of 2.25 μΩ·cm when contacting TCOs at intermediate firing temperatures. c , and the particle size D 50 >1.3mm, SSA less than 0.7m 2 The median value r obtained from the traditional Ag powder of c The contact resistivity data are summarized in Figure 1 The box plot is shown.
[0201] Moreover, the silver powder proposed in the present invention achieves lower line resistivity or higher line conductivity compared to conventional silver powder used for higher temperature firing. These results are shown in Figure 2 The box plots shown show that the median value of the optimal Ag powder is 2.4 μΩ·cm, while the median value of the conventional Ag powder is 37.4 μΩ·cm. These results indicate that the proposed Ag powder should result in solar cells with lower series resistance and higher fill factor (FF) than conventional Ag powder.
[0202] Nano-sized Ag particles are costly, therefore, the proposed Ag powder used in the present invention achieves optimal performance, and the cost of the proposed Ag powder is similar to that of conventional fired Ag powder.
[0203] It should be noted that the embodiments disclosed in the present invention have alternative implementations. Accordingly, the present embodiments should be considered illustrative rather than restrictive. In addition, the claims should not be limited to the details given in the present invention, but have their full scope and equivalent scope.
Claims
1. A metallization paste, characterized in that: Include: 70% by weight or more of silver powder; 2.0 wt% or less of vanadium-containing glass systems; The specific surface area of the silver powder is 0.7 m 2 / g to 2.0 m 2 / g, average particle size 0.1 µm to 10 µm; The wt % is based on the weight of the metallization paste.
2. The metallization paste according to claim 1, characterized in that: Based on the weight of the metallization paste, it also includes: 0.95 wt % or less of a silver powder surfactant coating, and / or 12 wt % or less of an organic carrier.
3. The metallization paste according to claim 1, characterized in that: Include: 70 to 95 wt % silver powder; 0.1 wt % to 2.0 wt % of a vanadium-containing glass system; 0.07 wt % to 0.95 wt % of a silver powder surfactant coating, The weight % is based on the weight of the metallization paste.
4. The metallization paste according to any one of claims 1 to 3, characterized in that: The vanadium-containing glass system is prepared from one or more metal oxides; The metal oxide contains vanadium pentoxide in an amount of 10-65 wt % based on the total weight of the metal oxide.
5. The metallization paste according to claim 4, characterized in that: The metal oxide is any one of vanadium pentoxide, silver oxide, tellurium dioxide, lead oxide, phosphorus oxide, and zinc oxide, or a combination of several of them.
6. The metallization paste according to claim 1, characterized in that: The vanadium-containing glass system has: Glass transition temperature T from 150°C to 400°C g ; Softening point of 200°C to 400°C; Average particle size from 0.1 µm to 20 µm.
7. The metallization paste according to claim 4 or 5, characterized in that: The vanadium-containing glass system is prepared by the following steps: The metal oxides are combined, the mixture of the metal oxides is heated to 800° C. to 1300° C. for 30 to 100 minutes, and then quenched and subsequently ground to obtain glass particles with a desired diameter and particle size distribution, that is, a vanadium-containing glass system.
8. The metallization paste according to claim 2, characterized in that: It contains 0.5 wt % to 10 wt % of an organic carrier; the organic carrier contains an organic binder, an organic solvent, and one or more additives; the additives include dispersants, thixotropic agents, plasticizers, viscosity stabilizers, defoaming agents, surfactants, pigments, UV stabilizers, antioxidants, coupling agents, and any combination of the foregoing.
9. The metallization paste according to claim 1, characterized in that: The specific surface area of the silver powder is 0.7 m 2 / g to 1.3 m 2 / g; Preferably, the specific surface area of the silver powder is 0.8 m 2 / g to 1.1 m 2 / g.
10. The metallization paste according to claim 1, characterized in that: The average particle size of the silver powder is 0.1 µm to 5 µm; Preferably, the average particle size of the silver powder is less than 2.0 µm; More preferably, the average particle size of the silver powder is 0.1 µm to 1.0 µm; Most preferably, the average particle size of the silver powder is 0.7 µm to 0.9 µm.
11. The metallization paste according to claim 2, characterized in that: The silver powder surfactant coating is selected from any one of oleic acid, palmitoleic acid, n-hexadecenoic acid, cis-10-heptadecenoic acid or a combination of several thereof.
12. The metallization paste according to any one of claims 1 to 11, characterized in that: The curing temperature of the metallization paste is 350°C to 500°C.
13. An electrode prepared by the metallization slurry according to any one of claims 1 to 11.
14. The electrode according to claim 13, characterized in that The electrodes are electrically interconnected with the transparent conductor.
15. A method for manufacturing an electrode, characterized in that: The following steps are involved: The metallization paste according to any one of claims 1 to 11 is deposited on a transparent conductor, and cured at a temperature of 350° C. to 500° C. for 5 to 90 minutes to form an electrode electrically interconnected with the transparent conductor.
16. The electrode according to claim 14, characterized in that The median contact resistivity of the electrical interconnection is less than 10 mΩ·cm; preferably, the median contact resistivity of the electrical interconnection is less than 5 mΩ·cm; more preferably, the median contact resistivity of the electrical interconnection is less than 3 mΩ·cm.
17. The electrode according to claim 14, characterized in that The peel strength of the electrode to the transparent conductor was greater than 2N as measured by a pull-out strength tester in a case where a copper solder coated strip was soldered to the electrode and the strip was pulled out at 180°.
18. The electrode according to claim 14, characterized in that The line resistivity of the electrode is less than 3 µΩ·cm.
19. The electrode according to claim 14, characterized in that The transparent conductor has a thickness of 10 nm to 250 nm.
20. The electrode according to claim 14, characterized in that The transparent conductor is indium tin oxide.
21. The vanadium-containing electrode manufactured by the electrode manufacturing method according to claim 15.
22. A photovoltaic cell, characterized in that: The photovoltaic cell comprises the vanadium-containing electrode of claim 21 interconnected with a transparent conductor.
23. An electronic device, characterized in that: The electrode comprises the electrode described in any one of claims 14 and 16-20.
24. The electronic device according to claim 23, characterized in that: The electronic device includes a photovoltaic cell.
25. The electronic device according to claim 24, characterized in that: The photovoltaic cell is a tunnel oxide passivated contact photovoltaic cell.
26. The electronic device according to claim 24, characterized in that: The photovoltaic cell comprises: A doped crystalline silicon substrate; a tunnel oxide layer covering the doped crystalline silicon substrate; An n+ polysilicon layer covering the tunnel oxide layer; a transparent conductor covering the n+ polysilicon layer; and A vanadium-containing electrode is in contact with the transparent conductor.
27. The electronic device according to claim 26, characterized in that: Also includes: A passivation layer covers the n+ polysilicon layer, and the transparent conductor covers the passivation layer.
28. The electronic device according to claim 27, characterized in that: The passivation layer contains Al2O3.
29. The electronic device according to claim 24, characterized in that: The photovoltaic cell comprises: A doped crystalline silicon substrate; a tunnel oxide layer covering the doped crystalline silicon substrate; A p+ polysilicon layer covering the tunnel oxide layer; a transparent conductor covering the p+ polysilicon layer; and A vanadium-containing electrode is in contact with the transparent conductor.
30. The electronic device according to claim 29, characterized in that Also includes: A passivation layer covers the p+ polysilicon layer, and the transparent conductor covers the passivation layer.
31. The electronic device according to claim 30, characterized in that: The passivation layer contains Al2O3.
32. The electronic device according to claim 24, characterized in that: The photovoltaic cell comprises: an n-doped silicon substrate comprising a front surface and a back surface; an anti-reflective coating covering the front surface; a tunnel oxide layer covering the back surface, wherein the tunnel oxide layer comprises a first portion and a second portion; an n+ polysilicon layer overlying the first portion of the tunnel oxide layer; a p+ polysilicon layer overlying the second portion of the tunnel oxide layer; A first transparent conductor covering the n+ polysilicon layer; A second transparent conductor covering the p+ polysilicon layer; a first vanadium-containing electrode grid in contact with the first transparent conductor; and A second vanadium-containing electrode grid is in contact with the second transparent conductor.
33. The electronic device according to claim 24, characterized in that: The photovoltaic cell comprises: a doped silicon substrate having a front surface and a back surface; a doped emitter layer overlying the front surface; a passivation layer covering the doped emitter layer; an anti-reflection layer covering the passivation layer; an electrode in contact with the doped emitter layer; a tunnel oxide layer overlying the back surface; a doped polysilicon layer covering the tunnel oxide layer; a transparent conductor overlying the doped polysilicon layer; and A vanadium-containing electrode is in contact with the transparent conductor.
34. The electronic device according to claim 33, characterized in that: The doped emitter layer includes a p+ doped emitter layer.
35. The electronic device according to claim 33, characterized in that: The anti-reflection layer comprises SiN x .
36. The electronic device according to claim 24, characterized in that The electronic device includes a touch panel, a display, a liquid crystal display, a light emitting diode, an organic light emitting device, a photodetector, a photoelectric device, a plasma device, a thin film transistor, an organic electronic device, an electromagnetic radiation sensor, a chemical sensor or a tactile sensor.
Citation Information
Patent Citations
Metal pastes and use thereof in the production of silicon solar cells
CN102365689A
Interdigitated back contact metal-insulator-semiconductor solar cell with printed oxide tunnel junctions
CN108575097A
Heterojunction solar cell and preparation method therefor
CN110168750A
Positive silver paste suitable for positive aluminum oxide-silicon nitride laminated passivation crystalline silicon solar cell and preparation method of positive silver paste
CN111128436A
Glass powder suitable for crystalline silicon p + layer contact and used for thick film silver paste and preparation method of glass powder
CN114380507A